Statistical/Dynamic approach to assess the effects of industrial fire - Chettouh, Samia; Hamzi, Rachida (11ème Congrès International Pluridisciplinaire en Qualité, Sûreté de Fonctionnement et Développement Durable, 2015)
In this paper, we will combine a statistical analysis of accident cases concerning the Algerian Oil and Gas Industry occurred during the period of 2003 to 2013 to a dynamic analysis based on the use of a numerical dispersion model. This combination lies in the use of the information obtained from the statistical analysis as input data in the Numerical Dispersion Model (NDM). This study may be useful to illustrate what the industry should learn from these accidents and in such a way be more alert to prevent future major accidents